Efficacy of topical imiquimod 3.75% in the treatment of actinic keratosis of the scalp in immunosuppressed patients: our case series. (2nd April 2020) - Zavattaro, E.; Veronese, F.; Landucci, G.; Tarantino, V.; Savoia, P.
Abstract: Background: Actinic keratoses (AK) represent common cutaneous lesions, appearing in 'Field cancerization areas' and potentially evolving toward invasive neoplasm. Immunosuppressed patients frequently develop numerous and aggressive AKs. Aim: In this observational study, we report our experience with topical Imiquimod 3.75% as 'Field-directed therapy' in a cohort of immunosuppressed patients. Methods: A group of 13 immunosuppressed patients presenting multiple AKs of the balding scalp was treated with topical Imiquimod 3.75%. Each patient underwent clinical examination at fixed timepoints during the treatment (T0, T14, T28, T42) and eight weeks after the end. Results: In our cohort, the treatment was well tolerated, with minimal local adverse events. We observed a good clinical response, in terms of Lmax lesions (maximum lesion count during the course of therapy) and of AK clearance. In our group, 46% of patients showed no detectable lesions at the end of the observation period, and this result was maintained up to 1 year after the end of treatment. Conclusion: Topical Imiquimod 3.75% represents an effective and safe treatment for multiple AK of the scalp also in immunosuppressed patients. To the best of our knowledge, this is the first report on the use of this drug in this category of subjects.